Agriculture and Structural Transformation in Africa: An Overview. (3rd August 2017) - Senbet, Lemma W.; Simbanegavi, Witness
Abstract: Agriculture is the mainstay of most African economies and economic performance in these countries is intricately linked to the performance of the agricultural sector. Indeed, in sub-Saharan Africa (SSA), the majority of the population resides in rural areas and the majority of farmers (up to 80%) are smallholders. However, productivity of these smallholder farmers is low compared to other developing regions, and this has perpetuated poverty in rural Africa. Agriculture has the greatest potential to reduce poverty in rural Africa. This special issue looks at efforts to transform agriculture in rural SSA to not only raise incomes of farmers, but to also foster broader structural transformation of African economies. The focus is on what needs to be done from a policy and practical point of view to kick-start, and in some cases, entrench structural transformation of the agricultural sector, taking cognizance of the need to transform across the value chain. Commitment by African governments, through initiatives such as the Comprehensive Africa Agriculture Development Programme, is a starting point. Over and above this, there is need to better understand why smallholder farmers are reluctant to invest in modern agricultural technologies, including use of modern seeds and fertilisers. Further, there are several constraints to be overcome for structural transformation of African agriculture to be a reality. These include: investing in development and diffusion of new and appropriate agricultural technologies; investing in infrastructure, including irrigation; addressing post-harvest challenges that small holder farmers face, etc. To better entrench the impacts, structural transformation in agriculture should happen concurrently with structural transformation of the rest of the economy, thus allowing for better allocation of scarce resources throughout the economy.